Self-Examination Low-Cost Full-Field Optical Coherence Tomography (SELFF-OCT) for neovascular age-related macular degeneration: a cross-sectional diagnostic accuracy study - Peter Koch; Inke König; Johann Roider; Jan Tode; Konstantine Purtskhvanidze; Claus von der Burchard; Helge Sudkamp; Cristoph Ehlken; Moritz Moltmann; Britta Heimes; Michael Münst; Malte vom Endt; et al. (BMJ Open)
Objectives Self-Examination Low-Cost Full-Field Optical Coherence Tomography (SELFF-OCT) is a novel OCT technology that was specifically designed for home monitoring of neovascular age-related macular degeneration (AMD). First clinical findings have been reported before. This trial investigates an improved prototype for patients with AMD and focusses on device operability and diagnostic accuracy compared with established spectral-domain OCT (SD-OCT).Design Prospective single-arm diagnostic accuracy study.Setting Tertiary care centre (University Eye Clinic).Participants 46 patients with age-related macular degeneration.Interventions Patients received short training in device handling and then performed multiple self-scans with the SELFF-OCT according to a predefined protocol. Additionally, all eyes were examined with standard SD-OCT, performed by medical personnel. All images were graded by at least 2 masked investigators in a reading centre.Primary outcome measure Rate of successful self-measurements.Secondary outcome measures Sensitivity and specificity of SELFF-OCT versus SD-OCT for different biomarkers and necessity for antivascular endothelial growth factor (anti-VEGF) treatment.Results In 86% of all examined eyes, OCT self-acquisition resulted in interpretable retinal OCT volume scans. In these patients, the sensitivity for detection of anti-VEGF treatment necessity was 0.94 (95% CI 0.79 to 0.99) and specificity 0.95 (95% CI 0.82 to 0.99).Conclusions SELFF-OCT was used successfully for retinal self-examination in most patients, and it could become a valuable tool for retinal home monitoring in the future. Improvements are in progress to reduce device size and to improve handling, image quality and success rates.Trial registration number DRKS00013755, CIV-17-12-022384.